2020
DOI: 10.3390/ma13020279
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Reducing the Toxicity of Metal and Metal Oxide NPs as Biomedicine

Abstract: The rapid development of medicine has forced equally rapid progress in the field of pharmaceuticals. In connection with the expensive and time-consuming process of finding new drugs, great emphasis is put on the design and use of metal and metal oxides nanoparticles in nanomedicine. The main focus is on comprehensive presentation of both physicochemical properties and the possibilities of using, in particular, silver (Ag) and gold (Au) nanoparticles, as well as zinc oxide (ZnO) and titanium oxide (TiO2) nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 82 publications
0
71
0
Order By: Relevance
“…Different approaches are available for reducing the toxicity of MNCs such as by altering their shape and size, or modifying their surface to retain essential properties but without creating toxicity. [ 180,181 ] Two factors significantly affect the stability of MNCs when they are used as drug carriers, namely, high salt levels of salt and presence of different proteins. High salt concentration decreases electrostatic repulsion between MNCs and causes them to aggregate.…”
Section: Affecting Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Different approaches are available for reducing the toxicity of MNCs such as by altering their shape and size, or modifying their surface to retain essential properties but without creating toxicity. [ 180,181 ] Two factors significantly affect the stability of MNCs when they are used as drug carriers, namely, high salt levels of salt and presence of different proteins. High salt concentration decreases electrostatic repulsion between MNCs and causes them to aggregate.…”
Section: Affecting Parametersmentioning
confidence: 99%
“…Conversely, proteins that are uptaken by the MNCs contribute to alterations in size and surface charge of the modified nanocompounds. [ 181 ] Understanding the interactions of MNCs with biological media is crucial for their safe applications in medical diagnostics and treatment. In the following subsections, the most important parameters that affect the biological activity of nanometals will be discussed.…”
Section: Affecting Parametersmentioning
confidence: 99%
“…These toxicity concerns are particularly relevant in vulnerable life stages such as pregnancy, infancy, infective, and inflammatory conditions. Changing the size, charge, shape, and appropriate functionalization of these nanoscale molecules with NO reactive groups and biotin, streptavidin, or PEG modifications will enhance their biocompatibility 125,128 . Minimizing the toxicity effects of such sensors will enhance their potential for clinical translation.…”
Section: Challenges In Clinical Translation Of No Bioimagingmentioning
confidence: 99%
“…However, extensive studies suggested that direct contact with metal and metal oxide NPs induced toxic effects to, for example, cardiovascular (Cao et al, 2018), central nervous (Chang, Li, Niu, Xue, & Tang, 2020), and pulmonary systems (Djurišić et al, 2015), which suggested a risk of metal and metal oxide NP exposure. As such, extensive studies are developing biocompatible metal and metal oxide NPs by, for example, controlling morphology and surface coating (Długosz, Szostak, Staroń, Pulit‐Prociak, & Banach, 2020). Besides these methods, developing nanocomplexes based on metal and metal oxide NPs is also a possible way to fabricate biocompatible NPs (Ghaemi et al, 2018; Yorseng, Siengchin, Ashok, & Rajulu, 2020).…”
Section: Introductionmentioning
confidence: 99%